The effect of early colonized gut microbiota on the growth performance of suckling lambs - Xiao, Hanjie; Yan, Hui; Tian, Peizhi; Ji, Shoukun; Zhao, Wen; Lu, Chensi; Zhang, Yingjie; Liu, Yueqin (Frontiers in Microbiology, 2023)
The early colonized gut microbiota during the newborn period has been reported to play important roles in the health and immunity of animals, however, would they can affect the growth performance of suckling lambs is still unclear. In this study, a total of 84 newborn lambs were assigned into LF-1 (top 15%), LF-2 (medium 70%), and LF-3 (bottom 15%) groups according to their average body weight gain at 30 days of age. Fecal samples of lambs (LF) as well as feces (MF), vagina (VAG), colostrum (COL), teat skin (TEAT) samples of ewes and the air sediment (AIR) in the delivery room, were collected at 72 hours after birth, then 16S rRNA gene was sequenced on the Illumina MiSeq platform. The results showed that the early colonized gut microbiota had a significant effect on the growth performance of suckling lambs with alpha and beta diversity (P < 0.05), and we observed the contribution of early colonized bacteria on the growth performance of lambs increased with age increased (from BW30 at 25.35% to BW45 at 31.10%; from ADG30 at 33.02% to ADG45 at 39.79% by measuring the relative effects of factors that influence growth performance). The early colonized gut microbiota of suckling lambs with high growth performance was similar to that in VAG, MF, and AIR (P<0.05). With RandomForest machine learning algorithm, we detected 11, 11, 6, and 4 bacterial taxa at genus level that associated with BW30, BW45, ADG30, and ADG45 of suckling lambs, respectively, and the correlation analysis showed that Butyricicoccus, Ruminococcus_gnavus_group, Ruminococcaceae_Other and Fusobacterium could significantly affect growth performance (BW30, BW45, ADG30, and ADG45) of suckling lambs (P < 0.05). In conclusion, the early colonized gut microbiota could significantly affect the growth performance of suckling lambs, targeting the early colonized gut microbiota might be an alternative strategy to improve the growth performance of suckling lambs.